The oak tree - Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
The oak tree The text titled The Oak Tree is a true story told by Kazimiera, a woman who in 1941 saw the bodies of murdered Jews being dumped into a common grave in a forest in Western Poland. This text refers to the work of memory and to the work of narration in the context of representation of the Holocaust. This text opens a question about the limits of commemorating and abusing of the past hidden in words and in silence.